Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41419-022-04909-3
|View full text |Cite
|
Sign up to set email alerts
|

TOPK/PBK is phosphorylated by ERK2 at serine 32, promotes tumorigenesis and is involved in sorafenib resistance in RCC

Abstract: TOPK/PBK (T-LAK Cell-Originated Protein Kinase) is a serine/threonine kinase that is highly expressed in a variety of human tumors and is associated with poor prognosis in many types of human malignancies. Its activation mechanism is not yet fully understood. A bidirectional signal transduced between TOPK and ERK2 (extracellular signal-regulated kinase 2) has been reported, with ERK2 able to phosphorylate TOPK at the Thr9 residue. However, mutated TOPK at Thr9 cannot repress cellular transformation. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Janus kinase 2 (JAK2) mediates Burkitt lymphoma growth by phosphorylating TOPK at Y74 [32]. TOPK is also a direct downstream substrate of ERK2, which is activated by direct phosphorylation of TOPK at S32, and after activation, TOPK plays an important role in sorafenib resistance in renal cell carcinoma (RCC) [33]. In our study, the application of TOPK inhibitor OTS514 in FYN overexpressing cells could signi cantly inhibit the proliferation and migration ability of GC cells induced by FYN.…”
Section: Discussionmentioning
confidence: 81%
“…Janus kinase 2 (JAK2) mediates Burkitt lymphoma growth by phosphorylating TOPK at Y74 [32]. TOPK is also a direct downstream substrate of ERK2, which is activated by direct phosphorylation of TOPK at S32, and after activation, TOPK plays an important role in sorafenib resistance in renal cell carcinoma (RCC) [33]. In our study, the application of TOPK inhibitor OTS514 in FYN overexpressing cells could signi cantly inhibit the proliferation and migration ability of GC cells induced by FYN.…”
Section: Discussionmentioning
confidence: 81%
“…Frontiers in Genetics frontiersin.org PDZ-binding kinase (PBK) is a serine/threonine kinase belonging to the mitogen-activated protein kinase (MAPK) kinase (MAPKK) family (Sun et al, 2016). Previous studies have shown that PBK is highly trans-activated in various cancers including ovarian cancer (Ma et al, 2022), lymphoma (Wang et al, 2022), kidney cancer (Sun et al, 2022), and colon cancer (Koshino et al, 2022), which is a promising molecular target for cancer-targeted therapy. It is worth mentioning that Yang et al (2019) found that PBK was overexpressed in HCC and was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…ERK activation can trigger a large transcriptional programme to support cell proliferation, suppress proapoptotic factors and stimulate antiapoptotic proteins [ 38 40 ]. ERK2 can phosphorylate TOPK/PBK to promote tumorigenesis and participate in sorafenib resistance of renal cancer [ 41 ]; ERK2-induced PDHE1α phosphorylation and subcellular translocation promote tumor immune escape [ 42 ]. In this study, we found that TJP2 and ERK2 are also low expressed in ccRCC, and their decreased expression is also related to worse pathology and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%